VD_FINDINFO HC / 2018 / 860 vom 2. Oktober 2018 - VD Tribunal cantonal (2018)
RESPONSABILITÉ DU PROPRIÉTAIRE D'OUVRAGE, INDUSTRIE DU VERRE, DÉFAUT DE LA CHOSE | 150 CO, 42 CO, 58 al. 1 CO, 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 107 al. 1 let. a CPC (CH), 308 al. 1 let. a CPC (CH)